Radical pair kinetics in a magnetic field - Till, U; Hore, P (1997)
Exact analytical expressions for the evolution of a non-diffusing spin-correlated radical pair in a strong magnetic field are presented. The recombination of singlet and triplet pairs at different rates, and the coherent evolution caused by magnetic interactions, lead to radical pair concentrations which are the sum of four time-dependent terms: two decaying exponentials and two exponentially damped oscillations. The predicted time dependence is used to illuminate the recombination dynamics of the primary radical pair in photosynthetic bacterial reaction centres. Although mono-exponential decay is expected ∼20 ns after the formation of each individual radical pair, the inhomogeneous distribution of Larmor frequencies of the two electron spins leads to non-exponential kinetics and different time constants for the disappearance of singlet and triplet pairs, and the formation of singlet and triplet recombination products.